Биология морских сельдей в раннем онтогенезе - Душкина Ладда Арсеньевна (Наука, 1988)
Экземпляры: КХ (20161119) / Инвентарный номер: 911538 / Цена: 2.90 / Сис.шифр: 597 / Авт.знак: Д 86 / ГРНТИ: 34.33.33 / ББК: 28